Biostimulants with glycine betaine or kelp extract alleviate heat stress in red raspberry (Rubus idaeus) - Givemore Munashe Makonya; David R. Bryla; Michael A. Hardigan; Wendy Hoashi-Erhardt; Lisa Wasko DeVetter (Scientific Reports)
Abstract Biostimulants are an emerging and innovative class of products that may mitigate the adverse effects of extreme heat, but research on their efficacy in fruit crops is limited. This study addressed this knowledge gap by evaluating the performance of three biostimulants, FRUIT ARMOR™, Optysil®, and KelpXpress™ [active ingredients glycine betaine, silicon, and kelp (Ascophyllum nodosum) extract, respectively] applied to three raspberry genotypes exposed to high temperatures (Tmax ≥ 35 °C/day) inside a glasshouse. ‘Meeker’ consistently maintained high chlorophyll fluorescence (Fv/Fm) and photosynthesis under control and biostimulant treatments. However, Fv/Fm and photosynthesis of WSU 2188 and ORUS 4715-2 increased when treated with FRUIT ARMOR™. KelpXpress™ also improved the Fv/Fm and photosynthesis of WSU 2188. ‘Meeker’ and WSU 2188 plants treated with FRUIT ARMOR™ and KelpXpress™ accumulated more anthocyanins and exhibited greater shoot and total biomass than ORUS 4715-2. Results demonstrate genotype and biostimulants vary in their ability to mitigate heat stress over time. Superior performance of ‘Meeker’ under control and biostimulant treatments manifested in improved heat tolerance. Biostimulants improved WSU 2188 and ORUS 4715-2 thermotolerance by improving PSII, photosynthetic, and antioxidative capacities. Results indicate biostimulants containing glycine betaine and kelp (Ascophyllum nodosum) extract enhance thermotolerance and may contribute to climate resiliency among commercial fruit crops exposed to heat stress.